Intention to Use Fintech Lending among Gojek Online Drivers: The Role of Trust, Security, and Personal Innovation - Haryanti , Enny; Kusmayadi, Angga Kusuma (Universitas Muhammadiyah Pontianak, 2026)
The development of fintech lending services has become a financing alternative for workers in the informal sector in Indonesia, including online motorcycle taxi drivers; however, the factors driving the intention to use these services still show varying findings across different studies. Therefore, this study examines the role of interest rates, personal innovation, security, trust, and familiarity in influencing the intention to use fintech lending among online motorcycle taxi drivers in the Greater Jakarta area. The research was conducted using a quantitative approach through a survey of 260 respondents selected using purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software to test the measurement model and relationships among variables. The results indicate that trust, security, and personal innovation have a significant positive influence on the intention to use fintech lending, while interest rates and familiarity do not show a significant influence. The research model has moderate explanatory power, suggesting that usage decisions are more influenced by behavioral factors and risk perceptions than by economic considerations. These findings confirm that increased transparency, system reliability, and user trust are key factors in driving fintech adoption among informal sector workers. Further research is recommended to use a longitudinal design and include socioeconomic variables to enhance the model’s predictive power and allow the research findings to be more broadly generalized within the Indonesian context.